THE IMPACT OF THE ELECTRONIC INVOICE ON TAX REVENUES AND ITS IMPACT ON THE IRAQI TAX SYSTEM AN EMPIRICAL STUDY - Dlawar Qader Abbas; Ghaith Hakim Malik; Hayder Hussein Jawad (Scholars Digest Publishing, 2024)
The main objective of the research is to study and analyse the impact of the electronic invoice on the tax proceeds and their impact on Iraq's tax system and the impact of the electronic invoice on the elimination of tax evasion, thereby increasing tax revenues, thereby reducing the cost of the invoice and thereby reducing effort and time, The research reached a series of results, the most important of which is the moral effect between the application of the electronic invoice and the tax proceeds in the light of the digital transformation; The electronic invoice reduces the risk of tax evasion and increases the tax proceeds. and there is a moral impact between the application of the electronic invoice and the increase in tax earnings and the reflection thereof on Iraq's tax system, The electronic invoice helps improve the accuracy of the information, in addition to supplying the VAT collected to the State Treasury, The research recommends the need to apply the electronic invoice, take advantage of the benefits of digital transformation and the extent of its impact on tax revenues, reduce tax evasion and increase the efficiency of Iraq's tax system.
Keywords: electronic invoice - tax proceeds - tax system.